Beauty in Psychology: A Bibliometric Analysis - Polina A. Nosova; Alexandr A. Fedorov (Peoples' Friendship University of Russia (RUDN University), 2022)
The purpose of the study is to conduct a bibliometric analysis of psychological publications devoted to the phenomenon of beauty. The research material (2214 articles) was extracted from the Scopus bibliographic database. The VOSviewer and biblioshiny software tools were used to analyze the results and build a bibliometric map. The construction of a conceptual map made it possible to identify four clusters related to the study of beauty: (1) the bodily component of a person; (2) attractiveness; (3) aesthetic phenomena; and (4) sociocultural processes. Thematic clustering using the Walktrap algorithm identified four themes; with the theme with the highest density and centrality devoted to the study of attractiveness, in particular, physical attractiveness and facial attractiveness. Five countries (USA, UK, Germany, Canada, Australia) produced almost 3/4 of the total number of publications (74.2%). The contribution of Russian authors amounted to 17 articles (0.8%). Trend analysis shows that in recent years there has been a growing interest in social media, aesthetic emotions and values. It is concluded that the main phenomena that are associated with the concept of "beauty" and are studied in psychology are body image, attractiveness, physical attractiveness, facial attractiveness and aesthetics. The conducted analysis shows that beauty as a value, remaining an understudied category, is explored in the context of positive psychology.